Ductus venosus agenesis, two tipical clinical cases - Miyahira Yataco, Cesar (2017)
The ductus venosus agnesis is not infrequent. It has two forms of presentation, each with different prognosis each. In the absence of the ductus venosus, the flow needs to find new pathways. There are two options. The first is by an extrahepatic shunt or portosystemic bypass, and the other by an intrahepatic shunt that drains to the portal system. The last one has a better prognosis. In both cases, It is especially important to look for associated structural and chromosomal anomalies, as to determine prognosis. It is especially important is to explore the biliary venous system. In this article, we present two clinical cases, with each one of the variants, without association to chromosomal diseases.